2018
DOI: 10.1021/acs.analchem.8b00769
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3,4-ethylenedioxythiophene)–Poly(styrenesulfonate)-Coated Glassy-Carbon Electrode for Simultaneous Voltammetric Determination of Uranium and Plutonium in Fast-Breeder-Test-Reactor Fuel

Abstract: Uranium (U) and plutonium (Pu) contents in nuclear materials must be maintained to a definite level in order to get the desired performance of the fuel inside the reactor. Therefore, high accuracy and precision is an essential criterion for the determination of U and Pu. We already reported the voltammetric determination of Pu in the presence of U in fast-breeder-test-reactor (FBTR) fuel samples, but interfacial, coupled chemical reactions between U(IV) and Pu(IV) enhance the peak-current density of U(VI) redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The observed positions and quantity of the redox couples differ from the previously reported ones for U or Pu in literature for bare GC electrode and various conditions. [53][54][55] In particular, uranyl(VI) nitrate in conditions close to those of this study showed only one redox couple of U(VI)/U(V) in cathodic region at À0.01(ox) V/ À0.25(red) V (vs. Ag/AgCl). 53 A quite similar behavior with one redox couple of U(VI)/U(V) at À0.075/À0.2 V (vs. Ag/AgCl) was found for uranyl(VI) perchlorate on Pt electrode in aqueous solution of 0.1 M LiClO 4 .…”
Section: The U(vi) Moieties Uptake From the Gw And Swsupporting
confidence: 72%
See 3 more Smart Citations
“…The observed positions and quantity of the redox couples differ from the previously reported ones for U or Pu in literature for bare GC electrode and various conditions. [53][54][55] In particular, uranyl(VI) nitrate in conditions close to those of this study showed only one redox couple of U(VI)/U(V) in cathodic region at À0.01(ox) V/ À0.25(red) V (vs. Ag/AgCl). 53 A quite similar behavior with one redox couple of U(VI)/U(V) at À0.075/À0.2 V (vs. Ag/AgCl) was found for uranyl(VI) perchlorate on Pt electrode in aqueous solution of 0.1 M LiClO 4 .…”
Section: The U(vi) Moieties Uptake From the Gw And Swsupporting
confidence: 72%
“…graphene oxide (GO) or conducting polymer PEDOT-PSS) with or without pre-adsorbed radionuclide species. [53][54][55] In particular, in the case of GO layer with the pre-adsorbed uranyl deposited on GC electrode the position of U(VI)/U(V) redox couple shis to anodic region by around 205-250 mV in comparison to bare GC. 53 Moreover, the shape of the peaks became more complicated and additional weakly pronounced redox couple at 0.21 V/0.13 V appeared that suggested both change of valence state of U and altering the electronic conguration of uranyl(VI) cations due to their coordination with functional groups on the GO surface.…”
Section: The U(vi) Moieties Uptake From the Gw And Swmentioning
confidence: 99%
See 2 more Smart Citations
“…The heterogeneous electron transfer reaction of Pu(IV)/Pu (III) is found to be an electrochemically quasi-reversible redox reaction, which greatly depends on the nature of the electrode materials. Hence, the electrochemistry of Pu (IV)/Pu(III) had been investigated on glassy carbon electrode [19], platinum electrode [20], and electrodes modified with platinum nanoparticles [10], ruthenium nanoparticles [21], poly(3,4-ethylenedioxythiophene) polystyrene sulfonate [22,23], polyaniline and single-walled carbon nanotubes [24], graphene [25], and electrochemically reduced graphene oxide [26]. However, none of the modified electrodes practically could be able to replace the conventional Pt electrode for the routine electrochemical analysis of Pu.…”
Section: Introductionmentioning
confidence: 99%